Selection of Acetic Acid Bacterial Strains and Vinegar Production From Local Maltese Food Sources - Mizzi, Joseph; Gaggìa, Francesca; Bozzi Cionci, Nicole; Di Gioia, Diana; Attard, Everaldo (Frontiers in Microbiology, 2022)
This study investigates the isolation, identification and fermentation performance of autochthonous Acetic Acid Bacteria (AAB) from local niche habitats in the Island of Gozo (Malta) and their further use for vinegar production, employing local raw materials. The bacteria were isolated from grapevine berries and from vinegar produced in cottage industry. The AAB following phenotype and genotype identification were ascribed to the genera Acetobacter, Gluconobacter and Komagataeibacter. A mixture of selected AAB was tested as inoculum for vinegar production in bench fermenters, under different conditions and substrates, namely grapes, honey, figs, onions, prickly pear and tomatoes. The bench fermenters were operated under semi-continuous fermentation where working volumes were maintained by discharging and subsequent recharging accordingly to maintain the acidity in fermenters between 30 g/l to 50 g/l acetic acid for optimal Acetobacteraceae performance. Finally, the vinegars from the different substrates were evaluated for their quality including organoleptic properties, showing the superior quality of wood-treated vinegars with respect to neat vinegars.